Incidencia de la articulación entre el SENA y los colegios oficiales de Bogotá en los resultados de las pruebas saber 11 de matemáticas y ciencias naturales entre el 2012 y el 2016 (2017)
The present research deals with the incidence of articulation between the National Learning Service -SENA- and the District Educational Institutions -IED- in the average results of the Saber 11 math and natural science tests between 2012 and 2016. For this purpose, It was used to make estimates by means of a panel of data by IED between 2012 and 2016 having as variable result the average of the tests Saber 11 of mathematics and natural sciences and as explanatory variables: to be or not articulated with the SENA, Type of productive sector associated with the supply, number of programs in each IED and number of eleven grade students who presented the Saber 11 test. For fixed effects of year and IED, it was found that the articulation between IED and SENA has no impact on the average results of the Saber 11 math and science tests, since all the estimates made are not statistically significant.